The Potsdam Agreement as Reflected in Peace Treaties - Klafkowski, Alfons (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
The paper is an English translation of Umowa poczdamska a traktaty pokoju by Alfons Klafkowski, published originally in Polish in “Państwo i Prawo” in 1966. The text is published as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Faculty of Law and Administration” devoted to the achievements of the late Professors of the Faculty of Law and Administration of the Adam Mickiewicz University, Poznań.